Drug Addiction 2008
DOI: 10.1007/978-0-387-76678-2_24
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Agonists and Antagonists of the Opioid Receptor-Like Receptor (ORL1, NOP): Ligand-Based Analysis of Structural Factors Influencing Intrinsic Activity at NOP

Abstract: A BSTRACTThe recently discovered fourth member of the opioid receptor family, the nociceptin receptor (NOP) and its endogenous ligand, the heptadecapeptide nociceptin, are involved in several central nervous system pathways, such as nociception, reward, tolerance, and feeding. The discovery of smallmolecule ligands for NOP is being actively pursued for several therapeutic applications. This review presents a brief overview of the several recently reported NOP ligands, classifi ed as NOP agonists and antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…As hypothesized in the SAR studies (see preceding text), this hydrophobic region of the binding pocket in the classic opioid receptors does allow for larger hydrophobic substituents, due to the smaller size of the amino acids and the greater flexibility of the aliphatic residues. It has also been hypothesized, based on the structures of several agonists and antagonists of the NOP receptor, that the lipophilic moiety at the piperidine nitrogen of Ro 64‐6198 is also important in determining agonist activity, such that agonist responses are produced because this lipophilic moiety occupies a binding site in the receptor that is located near the protonated piperidine (Zaveri et al 2005).…”
Section: Chemistry and Receptor Bindingmentioning
confidence: 99%
“…As hypothesized in the SAR studies (see preceding text), this hydrophobic region of the binding pocket in the classic opioid receptors does allow for larger hydrophobic substituents, due to the smaller size of the amino acids and the greater flexibility of the aliphatic residues. It has also been hypothesized, based on the structures of several agonists and antagonists of the NOP receptor, that the lipophilic moiety at the piperidine nitrogen of Ro 64‐6198 is also important in determining agonist activity, such that agonist responses are produced because this lipophilic moiety occupies a binding site in the receptor that is located near the protonated piperidine (Zaveri et al 2005).…”
Section: Chemistry and Receptor Bindingmentioning
confidence: 99%
“…We have synthesized and characterized several series of NOP ligands, many of which possess modest selectivity for NOP receptors ( Zaveri et al , 2004 ). We have carried out structure–activity relationship studies in several of our series, and reported that small changes in the piperidine nitrogen substituent can modulate agonist–antagonist activities of the NOP ligands ( Zaveri et al , 2005 ). Several ligands in our small molecule series also possessed significant affinity at μ‐ and some at κ‐opioid receptors ( Zaveri et al , 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Development of selective and highly potent peptide and nonpeptide agonist and antagonist ligands is of great importance for the understanding of the physiological and pathological roles of N/OFQ-NOP receptor system, too. Among them are N/OFQ-related peptides (Ambo, Kohara, Kawano, & Sasaki, 2007;Guerrini, Calò, et al, 2000;Naydenova, Todorov, Mateeva, et al, 2010;Guerrini, Calò, Bigoni, Rizzi, Regoli, & Salvadori, 2001;, small peptides, identified by screening of peptide combinatorial libraries (Dooley, Chung, Shiller, & Houghten, 1993;Dooley et al, 1997), and nonpeptide ligands such as Ro 64-6198 and JTC-801 (Zaveri, 2003;Zaveri, Jiang, Olsen, Polgar, & Toll, 2005). The synthesis of new NOP receptor ligands with higher affinity and lower enzymatic degradation is a primary goal of many research teams.…”
Section: Introductionmentioning
confidence: 99%